“Pengaruh Pengungkapan Emisi Karbon, Strategi Hijau, Biaya Lingkungan Terhadap Kinerja Perusahaan” - Farren Aldyaz Taris; Hasnawati (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This study aims to examine the effect of carbon emission disclosure, green strategy, and environmental cost on company performance. Mining companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023 served as the study sample. The sample was taken using a purposive sampling method, obtaining 158 companies that met the criteria. The data used in this study were obtained from annual reports and sustainability reports from the Indonesia Stock Exchange website and the company's official website. The results show that profitability has a positive effect on company performance. Leverage has a positive effect on company performance. Carbon emission disclosure has no effect on company performance. Green strategy has no effect on company performance. Environmental cost has no effect on company performance.